Mixed Ligand Complexes with 4-Aminoantipyrine Derivatives to Combat Natural Antioxidant System: Synthesis, Characterization and Biological Studies - Joseph, J.; Ayisha Bibin Rani, G. (Asian Journal of Chemistry, 2015)
Novel 4-aminoantipyrine based mixed ligand metal complexes with the Schiff bases of L1 (L1- 4-aminoantipyrine with furfuraldehyde and L2/L3/L4/L5 are and L2-2-aminophenol with salicylaldehyde, L3-2-aminophenol with cinnamaldehyde, L4-2-aminobenzothiazole with salicylaldehyde, L5-2-aminobenzothiazole with cinnamaldehyde) were synthesized. The structures of the mixed ligand complexes were established by analytical and spectral techniques. They were screened for in vitro antimicrobial activity against of bacteria and fungi by disc diffusion method. The interaction of metal complexes with calf thymus-DNA (CT-DNA) was investigated by UV-visible, cyclic voltammetry, viscosity and thermal denaturation studies. DNA interaction studies suggest that metal complex binds to calf thymus-DNA through intercalation mode. Superoxide dismutase activity of these complexes has also been studied. The free ligands and their metal complexes have been tested for in vitro antioxidant activity by the reduction of 1,1-diphenyl-2-picryl hydrazyl (DPPH). The antioxidant activities of the complexes were studied and compared with the activity of ascorbic acid. Copper(II) complex showed superior antioxidant activity than other complexes.